Lignocellulosic Biomass From Agricultural Residue For The Production Of Bioenergy And Bio-Based Materials - Sohni, Saima (2019)
The objectives of this study are to investigate physicochemical properties of wide range of agricultural residues available in Malaysia to ascertain their suitability for downstream processing along with prospective usage as promising feedstock in the production of bioenergy and bio-based materials. In the first phase, physicochemical characterization was carried out for oil palm frond (OPF), oil palm trunk (OPT), oil palm empty fruit bunch (EFB), oil palm kernel shell (PKS), rice husk (RH), rice straw (RS) and kenaf stalk (KF). These studies were based on proximate composition, CHNS/O content, calorific value and lignocellulosic content determination. In addition, various analytical techniques such as Fourier transform infrared (FTIR), X-ray diffraction (XRD), X-ray fluorescence (XRF) spectroscopy and thermogravimetry (TGA) were used to study microscopic properties such as functional groups, crystallographic structure, mineralogical composition and thermal degradation, respectively of these residues. Results of the first phase provided baseline for subsequent phases wherein two new eco-friendly processing methods using supercritical carbondioxide (SC-CO2) and tetrahydrofuran (THF) were demonstrated for OPT and PKS, respectively. Results of the first phase showed that in terms of volatile matter, the order followed was; EFB (83.42 %) ˃ KF (82.70 %) ˃ OPT (81.46 %) ˃ OPF (76.98 %) ˃ RS (76.42 %) ˃ PKS (69.66 %) ˃ RH (66.65 %), showing yield in thermochemical conversion. Proximate analysis revealed that RH has the highest ash content (18.82 %), predominantly composed of silica. The minimum ash material was generated by KF (5.73 %), EFB (6.56 %) and OPT (7.71 %), containing high fractions of catalytic species which are likely to participate in pyrolytic reactions.